State-dependent Riccati equation sliding mode observer for mathematical dynamic model of chronic myelogenous leukaemia. (2018) - Sharafian, Amin; Fard, Zeinab Ebrahimi
This paper is presented a new alternative technique by combination of state-dependent Riccati equation (SDRE) and sliding mode to overcome the problem of state estimation of chronic myelogenous leukaemia (CML). CML is one of the most common forms of cancer treated with children. The huge number of immune cells impairs the ability of these cells and cause defectiveness of medulla ossium ability to make red blood cells and platelets. Adopting SDRE technique in line with sliding mode observer could help us to achieve an optimum observer gain which prevent and reduce the observer system excitation and makes better estimation in CML dynamical model. SDRE technique brings certain non-linear parts of the system to a seemingly linear structure and avoids linearisation which reduces the accuracy of system. On the other hand, sliding mode applied to estimate disturbances. Combination of these techniques makes a better observer which benefit from both techniques features.